Partida: imersão criativa - Zequin, Ana Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The illustrated book is a reading that privileges the figure over the text, which may exist simultaneously or not in the narrative. In the picture book Departure the text was not necessary in the creative process. The proposal of this project in the arts was to create a narrative that, starting with a personal theme, gained structure in the course of different influences reaching the creative path. Gaston Bachelard, Pablo Neruda, Studio Ghibli, memoirs, my own production and other authors were part of the creative process of the book. For the development of the text was used the structuring of the creation in network, developed by the author Cecilia Almeida Salles

O livro ilustrado é uma leitura que privilegia a figura sobre o texto, podendo existir simultaneamente ou não na narrativa. No livro ilustrado Partida o texto não se fez necessário no processo criativo, o que, no Brasil, o caracteriza como um livroimagem. A proposta deste projeto em artes foi criar uma narrativa que, se iniciando em uma temática pessoal, ganhasse estrutura no decorrer que diferentes influências atingissem o percurso criador. Gaston Bachelard, Pablo Neruda, Studio Ghibli, memórias, a minha própria produção e outros autores fizeram parte do processo criativo do livro. Para o desenvolvimento do texto foi utilizado a estruturação da criação em rede, desenvolvido pela autora Cecilia Almeida Salles
Keywords: Livros artisticos; Criação (Literária, artística, etc.); Artes; Arts